2017
DOI: 10.5005/jp-journals-10025-1139
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Screening for Ectasia Risk prior to Laser Vision Correction

Abstract: Aim: To prospectively review current understanding and future trends of screening for keratectasia risk prior refractive laser vision correction (LVC).Background: Progressive keratectasia is an uncommon but severe complication of LVC. Preoperative ectatic corneal disease is the most important risk factor. Screening for subclinical ectasia relies on proper interpretation of advanced diagnostic technologies, including front surface corneal topography, three-dimensional tomography, and biomechanical assessments.S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Previous studies have reported an increase in CBI in eyes with ectasia. [ 13 23 ] However, the newer software allows an automatic assessment of the biomechanical stability post-laser vision correction using a new metric called CBI- Laser Vision Correction (LVC). CBI-LVC estimates the risk for ectasia after laser vision correction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported an increase in CBI in eyes with ectasia. [ 13 23 ] However, the newer software allows an automatic assessment of the biomechanical stability post-laser vision correction using a new metric called CBI- Laser Vision Correction (LVC). CBI-LVC estimates the risk for ectasia after laser vision correction.…”
Section: Discussionmentioning
confidence: 99%
“…To establish the risk of ectasia or subclinical keratoconus diagnosis, cut-off points were set for tomographic and biomechanical index. Based on Belin and Ambrósio 19 (for BAD), Vinciguerra et al 10 (for CBI) and Ambrósio et al 11 (for TBI), indexes were set on 1.2, 0.2 and 0.16, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Soft contact lens wearers were advised not to use them at least 7 days before preoperative assessment and hard contact lens wearers a longer period of 15 days prior to examinations, (10) anterior chamber depth (ACD) from endothelium ≥ 2.8 mm (11) endothelium cell density (ECD) ≥ 2000 cells/mm 2 . Exclusion criteria were: (12) hyperopia, (13) eye diseases, such as glaucoma and cataracts, (14) progressive corneal diseases, such as keratoconus or the presumed keratoconus and pellucid marginal degeneration (Topographical Keratoconus Classification ≥ 1), (15) ocular surface diseases, (16) signs of retinal vascular pathology, (17) immunodeficient patients or those diagnosed with connective tissue diseases, (18) pregnant or breastfeeding patients, (19) patients with known sensitivity to the drugs used in LVC or pIOL surgery, (20) patients with eye muscle disorders such as strabismus or nystagmus, or any other disorder that affects ocular fixation and ( 21) patients without visibility or with amblyopia in the other eye.…”
Section: Subjectsmentioning
confidence: 99%
“…14 Candidates for refractive surgery often have no to mild topographic changes that may progress to corneal ectasia after laser refractive surgery. 15 Scheimpflug corneal tomography is effective in detecting moderate to severe changes of the anterior corneal surface but has lower sensitivity in mild ectasia or fruste keratoconus.…”
Section: First Clinical Impressions On the Integrated Corneal Tomographymentioning
confidence: 99%